Word of Mouth, Observed Adoptions, and Anime-Watching Decisions: The Role of the Personal vs. the Community Network - Ameri, Mina; Honka, Elisabeth; Xie, Ying (Marketing Science, 2019)
This paper studies how word of mouth and product adoptions from friends and the whole community affect individuals’ product adoption decisions in the context of anime.